Chinese Dream and Practice in Zhejiang - Society - Chen, Guangjin; Yang, Jianhua (Research Series on the Chinese Dream and China's Development Path,, 2019)
The theme of this book is the society construction in Zhejiang Province under the guidance of "China Dream" policy. It adopts case studies, analysis, policy interpretations and practice summaries, presents the field practice and achievements in the local society. It exploits social studies areas such as social structure, public affairs management, urbanization, social security, as well as grassroots governance, society safety issues in the Zhejiang province. It also reveals a complete picture of the current society status in an analytical way. It helps scholars and political practitioners worldwide better understand how the "China Dream" policy has influenced the local Chinese society.